Ease of handling and physiological parameters of stress, carcasses, and pork quality of pigs handled in different group sizes - Dalla Costa, Filipe Antonio [UNESP]; Dalla Costa, Osmar Antonio; Castro, Izabela Cruvinel Di; Gregory, Neville George; Campos, Melissa Selaysim Di; Leal, Guilherme Brunno De Medeiros; Tavernari, Fernando De Castro (MDPI, 2019)
The effect of different group sizes of pigs (3, 5, and 10 pigs) during handling on physiological parameters, carcasses, and pork quality traits at the farm and slaughterhouse were evaluated in 360 pigs from five farms (four repetitions or group/treatment/farms). Data was analyzed as a factorial of 3 × 5 (3 treatments × 5 farms) to check effects of treatments by analysis of variance in ANOVA. Ease of handling decreased as the group size increased. However, time taken in handling was not influenced by the group size (p > 0.10). Moving pigs in groups of five animals reduced effects on blood cortisol levels (p < 0.05). Fighting and handling lesions in the carcasses increased for bigger handling groups (p < 0.05). Pigs handled in groups of three and ten animals had a higher pHu and initial temperature in Longissimus thoracis and Semimembranosus (p < 0.05) and lower drip loss in Semimembranosus (p < 0.05). However, meat quality classifications of the carcasses were not affected by treatments. Based on the results, moving groups of five pigs seems to be the best strategy to improve animal welfare, carcasses and pork quality.
Keywords: Cortisol; Lactate; Mounting; PH; Skin lesion